Pengaruh Metode Blanching Terhadap Kualitas Tepung Jamur Tiram Putih - Khathir, Rita; Yunita, Yunita; Ratna, Ratna; Elviana, Safira (Agriculture Faculty, 2023)
The study aimed to evaluate the influence of blanching methods to the quality of oyster mushroom flour. The treatments were non-blanching, hot water blanching and steam blanching at 3 replications. The amount of mushroom used for each treatment was about 500g. The mushroom was cut into cube shape sizing approximately 1cm. The drying process was conducted by using solar tunnel dryer type Hohenheim Aceh. The temperature and relative humidity were recorded by using proportional integral derivative (PID) controller connected to the outlet fans. The moisture was analyzed by using a moisture analyzer XY105MW, while color was examined by using a colorimeter LS171. The protein content of mushroom flour was determined by Kjeldahl method, and the ash content was identified by dry ashing method at temperature of 400-550C. Data were analyzed by using analysis of variance (ANOVA). Results showed that the blanching method could cut the drying time approximately for 3h. The ANOVA had shown a significant influence of blanching methods to the moisture, yield, ash content and whitness index (WI). However, there is no significant influence of treatments to the protein content. This study suggests the hot water blanching in processing the oyster mushroom flour because it produced the best performance of oyster mushroom flour i.e moisture of 5.78%, yield of 6.26%, protein content of 19.32%, ash content of 4.99% and whitness index of 63.88. Further study is necessary to determine the best combination of temperature and drying time in order to increase the yield.